Pig Hunting Tradition in Nagari Panta Pauh Matur District Agam Regency West Sumatra - Tasya, Natasya Aulia Putri; Yurisman; Emzia Fajri (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This study entitled "The Tradition of Pig Hunting in Nagari Panta Pauh, Matur District, Agam Regency, West Sumatra". The purpose of this study was to describe the implementation of the traditional pig hunting activities and the function of the pig hunting tradition for the community in Nagari Panta Pauh, Matur District, Agam Regency. The theory used in this thesis is the functionalism theory of Bronislaw Malinowski. The method that the author uses is a qualitative method, with data collection techniques namely observation, interviews and documentation.The results of the study found that there were two stages in carrying out pig hunting, namely preparation before hunting and carrying out pig hunting. In hunting activities there are functions for the community that we can see, these functions are as follows: a) Environment, the tradition of hunting pigs in Nagari Panta Pauh functions as wild boar pest control. b) Recreation, hunting pigs is not only a hobby for hunters, but also gives satisfaction to those who do it. c) Social, there is cooperation, gathering events and social status. d) Culture, pig hunting can be seen as a form of negotiation against customary provisions which may prohibit men from carrying out certain activities. Through pig hunting, men can find a way to participate in the activities they enjoy without violating existing customary provisions. e) Economy, hunting also has benefits for people in hunting locations, namely by encouraging economic growth through trading activities that occuraround hunting locations.